Adenomyosis-a rare cause of chronic lumbago in adolescents - Yogini, Kavitha; Maran, Varsha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Adenomyosis is a benign condition of the uterus that was previously diagnosed through histology after hysterectomy. Specifically, ectopic endometrial glands and stroma were seen at a minimum depth of 2.5 mm below the Endo myometrial junction, along with hypertrophic and hyperplastic surrounding myometrium. Adolescent adenomyosis is not known to occur frequently. Furthermore, in extremely young individuals, the classic diagnostic indicators of adenomyosis may not be present during clinical, sonographic, or radiologic testing. Although cystic form of adenomyosis is more common in the younger age group, diffuse adenomyosis should always be considered in refractory pelvic pain. Ultrasound and MRI done together has improved sensitivity for the diagnosis of adenomyosis. Dienogest, the millennial molecule, not only serves its purpose in endometriosis but also one of the first line drugs in the management of adenomyosis, particularly the diffuse forms.